The Modernization of Islamic Institutions in North Sumatra during the Early Twentieth Century: The Development of Madrasahs and the Transformation of the Learning System - Ahmad Ibrahim Hasibuan (Local History & Heritage, 2026)
This article examines the historical trajectory of Islamic modernization in North Sumatra during the early twentieth century by analyzing the emergence of madrasas and the transformation of traditional learning systems amid colonial intervention, socio-religious reform, and the expansion of transregional intellectual networks. The study addresses how Islamic institutions evolved from surau- and pesantren-based instruction into structured madrasa systems and identifies the historical forces that shaped this transformation. Employing the historical method, the research applies heuristic, source-critical, interpretive, and historiographical methods using archival records, colonial reports, contemporary newspapers, organizational documents, and relevant secondary literature. The findings reveal that these primary historical sources demonstrate the modernization of madrasas as a multidimensional process driven not only by reformist ideas introduced by Middle Eastern-educated scholars and Islamic organizations but also by institutional responses to Dutch colonial educational policies. The establishment of graded classes, standardized curricula, secular subjects, and modern administration redefined patterns of knowledge transmission and strengthened the institutional position of Islamic education. This study argues that madrasa modernization constituted a broader process of social, intellectual, and religious transformation that reshaped the historical development of Islamic institutions in colonial North Sumatra.